Business Opportunities in Aircraft Cabin Conversion and Refurbishing - Mihaela Nita and Dieter Scholz (Journal of aerospace operations, 2011)
This paper identifies several meaningful business opportunity cases in the area of aircraft cabin conversion and refurbishing and predicts the market volume and the world distribution for each of them: 1) international cabins, 2) domestic cabins, 3) aircraft on operating lease, 4) freighter conversions and 5) VIP completions. This implies the determination of cabin modification/conversion scenarios, along with their duration and frequency. Factors driving the cabin conversion and refurbishing are identified. Several aircraft databases, containing the current world feet as well as the forecasted fleet for the next years, are analyzed. The results are obtained by creating a program able to read and analyze the gathered data. It is shown that about 38000 cabin redesigns will be undertaken within the next 20 years. About 2500 conversions from jetliners into freighters and 25000 cabin modifications at VIP standards will emerge on the market. The North American and European markets will keep providing good business opportunities in this area. The Asian market, however, is growing fast, and its very strong influence on demand puts it in the front rank for the next 20 years.
Keywords: aviation; aircraft; cabin; system; completion; upgrade; conversion; refurbishing; optimization; process; chain; market; forecast; database; scenario; interior; retrofit; outsourcing; manufacturer; business; opportunity; engineering; subcontracting; freighter; VIP